Healthy Lifestyle Behaviors Among Older U.S. Adults With and Without Disabilities, Behavioral Risk Factor Surveillance System, 2003 - Indu B. Ahluwalia, MPH, PhD; Catherine A. Okoro, MS; Tara W. Strine, MPH; Lisa C. McGuire, PhD; Earl S. Ford, MD, MPH (Centers for Disease Control and Prevention, 2007)
IntroductionLittle is known about the relationship between healthy behaviors and the prevalence of chronic diseases in older adults with disabilities. This study examines the prevalence of selected healthy lifestyle behaviors related to chronic diseases among adults aged 65 years and older with and without disabilities. MethodsData from the 2003 Behavioral Risk Factor Surveillance System (BRFSS) were used to assess having a healthy weight and six behaviors: current cigarette smoking status, consumption of at least one alcoholic beverage daily, consumption of at least five fruits or vegetables daily, physical activity during the average week, influenza immunization in the past year, and lifetime pneumococcal immunization. ResultsPeople with a disability were less likely than people without a disability to have a healthy weight (28.5% vs 37.2%) and to engage in the recommended level of weekly physical activity (14.7% vs 26.2%). However, people with a disability were more likely than those without a disability to be nonsmokers (91.8% vs 89.9%), to consume up to one alcoholic beverage daily (95.1% vs 91.5%), to have received their influenza immunization in the past year (72.7% vs 69.0%), and to have received a lifetime pneumococcal immunization (72.1% vs 63.0%). There was no difference between people with and without a disability in the prevalence rates of consuming at least five fruits or vegetables daily. ConclusionThe prevalence of having a healthy weight and six chronic-disease related behaviors among adults aged 65 years and older varies by disability status and by specific modifiable lifestyle behavior. Screening older adults with and without disabilities and counseling them about health behaviors should be integrated into every interaction between older adults and their health care providers to potentially lower the rates of morbidity and mortality related to chronic diseases in the later years.